Increased Insulin Requirements in Severe Cases of Covid-19 are Higher Than in Moderate Cases - Matsui T; Ushigome E; Hamaguchi M; Sudo K; Kitagawa N; Kondo Y; Hasegawa Y; Imai D; Hattori T; Yamazaki M; Sawa T; Fukui M (Diabetes, Metabolic Syndrome and Obesity, 2024)
Takaaki Matsui,1 Emi Ushigome,1 Masahide Hamaguchi,1 Kazuki Sudo,2 Nobuko Kitagawa,1 Yuriko Kondo,1 Yuka Hasegawa,1 Dan Imai,1 Tomohiro Hattori,1 Masahiro Yamazaki,1 Teiji Sawa,2 Michiaki Fukui1 1Department of Endocrinology and Metabolism, Graduate School of Medical Science, Kyoto Prefectural University of Medicine, Kyoto, 602-8566, Japan; 2Department of Anesthesiology, Graduate School of Medical Science, Kyoto Prefectural University of Medicine, Kyoto, 602-8566, JapanCorrespondence: Emi Ushigome, Department of Endocrinology and Metabolism, Graduate School of Medical Science, Kyoto Prefectural University of Medicine, 465, Kajii cho, Kamigyo-ku, Kyoto-city, Kyoto, 621-8585, Japan, Tel/Fax +81-75-251-5505, Email emis@koto.kpu-m.ac.jpPurpose: Despite the low overall death rate of coronavirus disease 2019 (COVID-19), no study has examined the association between COVID-19 severity and the total daily insulin dose required for glycemic control. The aim of this study was to determine the maximum total daily insulin dose required according to COVID-19 severity, and the number of days required to reach the maximum insulin dose in patients with COVID-19 who used insulin during hospitalization.Patients and Methods: This retrospective cohort study included participants aged 20– 90 years with a confirmed diagnosis of COVID-19 who used insulin during hospitalization at Kyoto Prefectural University of Medicine Hospital between March 4, 2020, and May 31, 2021. Factors associated with maximum insulin dose during hospitalization were evaluated using linear regression analyses.Results: The maximum insulin doses were 31.8, 76.8, and 230.7 U/day, and the numbers of days between COVID-19 diagnosis and the need for maximum insulin were 15.6, 17.1, and 13.7 days in patients without ventilator management, with ventilator management, and with ventilator and extracorporeal membrane oxygenation management, respectively. Multivariate linear regression analyses revealed that hemoglobin A1c level (β = 15.87, P = 0.001), use of a ventilator (β = 50.53, P < 0.001), and use of extracorporeal membrane oxygenation (β = 150.36, P < 0.001) were independent determinants of maximum insulin dose.Conclusion: Patients with severe COVID-19 required a significantly higher maximum insulin dose than did those with moderate COVID-19. The maximum insulin dose was reached approximately 2 weeks after onset. Furthermore, the hemoglobin A1c level on admission and the use of a ventilator or extracorporeal membrane oxygenation during hospitalization were associated with the need for maximum insulin dose.Plain language summary: Why was the study done?More than 769 million infections and 6.9 million fatalities have resulted from the coronavirus disease 2019 (COVID-19), which is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2).In relation to the degree of sickness, what is the maximum daily insulin dosage and the number of days required to achieve the maximum insulin dose?What did the researchers do and find?The maximum total daily insulin dose required according to COVID-19 severity and the number of days required to reach the maximum insulin dose in patients with COVID-19 who used insulin during hospitalization were determined in this study.The maximum daily insulin requirement in this study was reached approximately 2 weeks after the onset of COVID-19, regardless of severity.What do these results mean?The results of this study may be useful as an indicator of insulin dosage and incremental acceleration in future COVID-19 clinical practice.Predicting the maximum amount of insulin and the time required to reach this maximum during hospitalization will lead to more appropriate glycemic management.Keywords: COVID-related diabetes, SARS-CoV-2, insulin resistance, glycemic control, retrospective cohort study